Detecting short-term weathering of stone monuments by 3D laser scanning: lithology, wall orientation, material loss. - Fehér, Krisztina; Török, Ákos (Journal of Cultural Heritage, 2022)
• Short term non-linear weathering processes are detected by laser scanner. • Wall orientation and lithology control the weathering. • Ooidal porous limestone is more prone to weathering than bioclastic porous limestone. • Surfaces with alveolar weathering and granular disintegration can have a surface loss of up to 9 mm during one winter period. Stone deterioration is a non-linear process that is difficult to observe in a short period. The current study documents surface changes related to material loss using terrestrial laser scanner (TLS) and explains the differences in weathering of lithotypes and different wall orientations of various weathering forms. Ruins of a medieval church constructed from weathering-prone porous limestone were surveyed prior to and after a winter period in a five-month interval with two scan phases. Thirty-five stone surfaces of exposed and sheltered wall sections of different compass orientations were compared to assess the short-term material loss and weathering. The study revealed that more than 30% of the selected surfaces show a major surface retreat of more than 4 mm. Three to nine percent of the scanned areas show countable deterioration. The most significant material loss was recorded at rain exposed but partially wind protected walls facing Northeast. Lithology also controls the surface loss and the rate of weathering. Ooidal porous limestone is the most sensitive lithology to weathering. The minor heterogeneities of the stone ashlar and the co-existence of weathered and seemingly intact areas even within one stone block were also considered. Comparing two time-lapses allows for recognizing even minor surface loss. Scans could be made before and after the weathering threshold, but it cannot be predicted when the threshold is reached. [Display omitted]